Threatened fishes of the world: Anoxypristis cuspidata (Latham, 1794) (Pristidae) - Ali Reza Radkhah; Soheil Eagderi (Journal of Fisheries, 2019)
The knifetooth sawfish Anoxypristis cuspidata (Latham, 1794) is a species of sawfish belonging to the family Pristidae. It is an Indo-West Pacific species occurring from the northern Persian Gulf to Australia and north to Japan. The species is assessed as Endangered in the IUCN Red List of Threatened Species. Main threats to the species are fishing, coastal development and habitat degradation. This sawfish species has considerable ecological importance for the regions, but there are little data of its populations. Hence, a detailed study of population status, ecological and biological characteristics of A. cuspidata is required. This study will provide basic information on distribution, biological characteristics and conservation of this species.